Pengaruh Pengaku Konsentris (Concentric Bracing) dan Eksentris (Eccentric Bracing) pada Struktur Baja dengan Daktilitas PenuhTerhadap Gempa - Sumargo; Syamsul Basri; Anis Rosyidah (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2003)
This study evaluated concentric and eccentric braced-frame subjected to El Centro and Pasadena earthquake. The parameters examined were natural periods, story drift, hysteresis loop, element's and structure's ductility. The structures are 1 2-story steel frames with 4 (four) different bracing configurations, such as: diagonal concentric bracing (A1), inverted V concentric bracing (A2), diagonal eccentric bracing (B1) and inverted V eccentric bracing (B2). Structural Analysis Program (SAP 2000) Version 7.42 and Microsoft Excel had been used as analytical aids. The methodology in this study consisted of design stage and analysis of structure behavior. In order to examine structures behavior, the structures were analyzed using the same section properties. The result showed that BI frame has the largest natural period of 0,423 second and the lowest natural period is A2 frame of 0,362 second. Steel frame B2 has largest drift due to El Centro and Pasadena earthquake. This seismic load resulted in elastic behavior for all steel frame under consideration s0 as the structure ductility () —1. The same result of unit ductility was obtained for all elements since plastic hinge had not been developed.